2003
DOI: 10.1063/1.1600511
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of nanoceramics reinforced with ropes of single-walled carbon nanotubes

Abstract: Single-walled carbon nanotubes (SWCNTs) were used to convert insulating nanoceramics to metallically conductive composites. Dense SWCNT/Al2O3 nanocomposites with CNT contents ranging from 5.7 to 15 vol % and with nanocrystalline alumina matrices have been fabricated by spark-plasma-sintering that retains the integrity of SWCNT in the matrix. The conductivity of these composites increases with increasing content of CNTs. The conductivity has been increased to 3345 S/m in the 15 vol % SWCNT/Al2O3 nanocomposite a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
3
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(114 citation statements)
references
References 18 publications
4
93
3
2
Order By: Relevance
“…Samples with higher densities showed higher modulus as well as higher hardness and fracture toughness. Similar results have been obtained on introducing SWCNTs into alumina by SPS 70,71 ; apparently undamaged CNTs were incorporated at the grain boundaries, resulting in improved fracture toughness and bending strength (although see below for discussion). Table 1 summarises the mechanical properties of CNT/inorganic matrix composites reported in the literature, including a number of significant improvements achieved by addition of CNTs.…”
Section: Advanced Consolidation Techniquessupporting
confidence: 69%
See 1 more Smart Citation
“…Samples with higher densities showed higher modulus as well as higher hardness and fracture toughness. Similar results have been obtained on introducing SWCNTs into alumina by SPS 70,71 ; apparently undamaged CNTs were incorporated at the grain boundaries, resulting in improved fracture toughness and bending strength (although see below for discussion). Table 1 summarises the mechanical properties of CNT/inorganic matrix composites reported in the literature, including a number of significant improvements achieved by addition of CNTs.…”
Section: Advanced Consolidation Techniquessupporting
confidence: 69%
“…Powder processing has been applied to various composites systems including borosilicate glass 33,63 , silicon nitride 64-69 alumina, 70,71 , mullite 72 and silica 73 matrix composites containing different concentrations of CNTs (typically 1 -10 vol.%). These investigations have been of mixed success in terms of the quality of the microstructure homogeneity and properties achieved (see section 4).…”
Section: Powder Processingmentioning
confidence: 99%
“…CNTs have already demonstrated their role as a multi-functional filler for various ceramic [6][7][8][9][10][11][12] and polymer [13][14][15][16] nanocomposites. However, CNT aggregation during processing of such nanocomposites is one of the major obstacles for their successful exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…Such entangled bundles of CNTs cause significant reduction in the properties of ceramic nanocomposites [18]. Agglomerates of CNTs reduce the mechanical [13,[19][20][21] and electrical properties [11,20] of various nanocomposites. To date, colloidal processing [22][23][24] has proven to be the most successful way of producing homogeneous suspensions of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…With many publications in processing nanocrystalline aluminum oxide, Zhan et al, and Duan et al demonstrated improved fracture toughness, of upto three times than that of aluminum oxide, using spark plasma sintering consolidation of CNT-A1 2 0 3 composite, Fig 2.24 [125,166,171,[186][187][188][189][190][191]. However, the primary interest of Zhan et showing CNT pullout [11].…”
Section: Aluminum Oxide-cnt Nanocompositementioning
confidence: 99%